DESENTRALISASI FISKAL DI KOTA BANDUNG (Studi Tentang Pemungutan Pajak BPHTB Di Pemerintah Kota Bandung ) - Rachmat Satiadi (Jurnal Transformasi Administrasi, 2021)
The transfer of management duties on Acquisition of Land and Building (BPHTB) and Tax on Land and Building Rural and Urban (UN-P2) from the Central Government to Local Government is a form of follow-up policy of regional autonomy and fiscal decentralization. However, in practice, fiscal decentralization in BPHTB voting has not been done optimally. It thus appears from the results recap realization of Bandung where the local tax contribution to BPHTB still much to be expected. This study aims to identify and describe and explore issues relating to the effectiveness of fiscal decentralization, particularly the Customs Tax Acquisition of Land and Building in Bandung. The study, using a qualitative approach. The key informant consists of; The first, key informants consisting of officials at the Tax Office in Bandung; second, frontline staff that tax officers who serve directly the taxpayer; and the third is the taxpayer (tax payer) and Officer Deed Land (PPAT). The technique of collecting data through interviews, observation of the implementation of the activities of service providers in the tax office and documentation study. This study uses a theory promoted by the Fiscal Decentralization Delivery. The results showed that fiscal decentralization BPHTB tax collection in the city of Bandung has not been effective because it is not based to the principle of local autonomy, participation in a democratic, bottom-up planning, the generation of financial resources and balance the distribution of resources. In the implementation process required strengthening BPHTB tax on such policies Appraisal of every transaction through the online reporting; punish and reward system for taxpayers BPHTB; construction of space communication with stakeholders, associated with the allocation of tax dollars; empowerment for tax officials to carry out the functions of service according to the expectations of taxpayers; and the need to involve the taxpayer BPHTB to reduce the gap between expectation and reality about the quality of existing services.